2021
DOI: 10.3389/fpubh.2021.682975
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Salt Reduction, Prevalence of Hypertension and Avoidable Burden of Stroke in Vietnam: Modelling the Health and Economic Impacts

Abstract: Dietary salt reduction has been recommended as a cost-effective population-wide strategy to prevent cardiovascular disease. The health and economic impact of salt consumption on the future burden of stroke in Vietnam is not known.Objective: To estimate the avoidable incidence of and deaths from stroke, as well as the healthy life years and healthcare costs that could be gained from reducing salt consumption in Vietnam.Methods: This was a macrosimulation health and economic impact assessment study. Data on bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Factors including an increase in dietary salt, age over 60+ years, obesity, urban residence, low education, and high income were identified to be associated with an increased probability of exacerbation of hypertension status. 15,62–64 The findings from these studies indicated the implications of exploring the factors influencing the progression of hypertension severity. The current study is the first to assess the influence of DNA methylation.…”
Section: Discussionmentioning
confidence: 83%
“…Factors including an increase in dietary salt, age over 60+ years, obesity, urban residence, low education, and high income were identified to be associated with an increased probability of exacerbation of hypertension status. 15,62–64 The findings from these studies indicated the implications of exploring the factors influencing the progression of hypertension severity. The current study is the first to assess the influence of DNA methylation.…”
Section: Discussionmentioning
confidence: 83%
“…Despite compelling evidence on the relationship between dietary sodium, BP and CKD, few studies have assessed the long-term impact of sodium reduction on CKD burden [ 12 ]. Most modelling studies globally [ 13 , 14 , 15 , 16 , 17 ] and in Australia [ 18 , 19 ] have either focused on the impact on heart disease and stroke or did not explore the longer-term impacts on CKD [ 20 ]. This implies the currently reported health impacts of sodium reduction in Australia are likely underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent World Health Organization (WHO) STEPS survey in Vietnam estimated that adults consume on average 9.4 grams of salt per day (10), which is about double the current WHO recommendation of <5g/day (11). Existing research on the harmful effects of high salt intake globally (12) and in Vietnam (13, 14) has mostly focused on its impact on blood pressure and cardiovascular disease. The impact of such high salt diets on the burden of stomach cancer has not been evaluated in Vietnam.…”
Section: Introductionmentioning
confidence: 99%